The U.S. Needs a National Human Health Observing System - Sandifer, Paul A.; Singer, Burton H.; Colwell, Rita R. (Frontiers in Public Health, 2021)
• The COVID-19 pandemic and increasing frequency of environmental disasters reveal an urgent need for a health observing/surveillance system • With the possible exception of Brazil, we know of no such system • The US should create a national system of linked regionally-based health monitoring systems similar to those for weather, ocean conditions, and climate • Like those for weather, the health observing system should operate continuously, collecting mental, physical, and community health data before, during, and after events • The system should include existing cross-sectional health data surveys, along with significant new investment in regional longitudinal cohort studies • The recently described framework for a Gulf of Mexico Community Health Observing System is suggested as a potential model for development of a nation-wide system